1995
DOI: 10.1007/bf00004348
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol-17? suppresses testicular development and stimulates sex reversal in protandrous black porgy, Acanthopagrus schlegeli

Abstract: Two year old black porgy (Acanthopagrus schlegeli) fed a diet containing 4.0 mg kg(-1) of estradiol-17β (E2) for 5 months had significantly lower GSI than the control group during the spawning season. E2 suppressed testicular development, spermiation and plasma testosterone (T) and 11-ketotestosterone (11-KT) and stimulated ovarian development, vitellogenesis and sex reversal. Spermiation in the control group occurred in January and February with the concentrations of 1.08-1.36 × 10(10) sperm ml(-1) of milt. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 28 publications
2
46
0
Order By: Relevance
“…No clear boundary (connective tissue) was formed in fish in the first year. Primary oocytes could develop from testicular tissue when estradiol was given to black porgy for a 1-2 month period in 1-and 2-year-old fish (Chang et al, 1995a(Chang et al, , 1995b. Therefore, low levels of Dmrt1 transcripts could be detected in the bisexual ovary of 1+ year-old fish because of the similarity and same origin of testicular and ovarian tissue.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…No clear boundary (connective tissue) was formed in fish in the first year. Primary oocytes could develop from testicular tissue when estradiol was given to black porgy for a 1-2 month period in 1-and 2-year-old fish (Chang et al, 1995a(Chang et al, , 1995b. Therefore, low levels of Dmrt1 transcripts could be detected in the bisexual ovary of 1+ year-old fish because of the similarity and same origin of testicular and ovarian tissue.…”
Section: Discussionmentioning
confidence: 96%
“…We previously found that estradiol, aromatase, estrogen receptor and androgen receptor were correlated with the control of the natural sex change in black porgy (Chang et al, 1994(Chang et al, , 1995a(Chang et al, , 1995bChang and Lin, 1998;Lee et al, 2002;He et al, 2003). Therefore, endocrine factors are suggested to be involved in the process of sex change in black porgy (Lee et al, 2001).…”
mentioning
confidence: 99%
“…Several studies have highlighted the importance of estrogens and the aromatase pathway in the gonadal sex change processes (Cardwell and Liley 1991;Cochran and Grier 1991;Godwin and Thomas 1993; Chang et al 1994Chang et al ,1995;Kroon and Liley 2000; Kroon et al 2003) and have suggested that it is a decrease in E 2 levels that permits male development (Kroon et al 2005). Similarly, we found that when the estrogen synthesis blocker 1,4,6-androstatrien-3,17-dione (ATD) is given alone or coadministered with T, complete color and gonadal sex change is induced in female T. bifasciatum (Austin et al unpublished).…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneous hermaphrodites (Fisher, 1987;Fisher and Hardison, 1987) often have mature ovotestes allowing the "male/female" to change quickly in response to environmental conditions such as spawning behaviors of potential mates. By contrast, the more common sequential hermaphrodites show extensive restructuring and redevelopment of the existing reproductive system (Nakamura et al ., 1989;Cardwell and Liley, 1991) or a simultaneous regression and recrudescence of the respective portions of the gonad (Chang et al ., 1995).…”
Section: Introductionmentioning
confidence: 99%